2011
DOI: 10.1007/s11596-011-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of post-stroke dysphagia by vitalstim therapy coupled with conventional swallowing training

Abstract: To investigate the effects of VitalStim therapy coupled with conventional swallowing training on recovery of post-stroke dysphagia, a total of 120 patients with post-stroke dysphagia were randomly and evenly divided into three groups: conventional swallowing therapy group, VitalStim therapy group, and VitalStim therapy plus conventional swallowing therapy group. Prior to and after the treatment, signals of surface electromyography (sEMG) of swallowing muscles were detected, swallowing function was evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 26 publications
1
72
0
5
Order By: Relevance
“…In a study by Xia et al (2011), 120 post stroke patients who exhibited dysphagia were randomly assigned to receive either traditional swallowing treatment, solely NMES, or NMES in conjunction with traditional swallowing management. (67)The researchers found that the individuals who received NMES along with traditional treatment made significantly greater improvements in all four-outcome measures, as opposed to the group who received traditional treatment alone or the group who received NMES alone. Another study by Kushner, et al (2013) examined the effect of NMES use with feeding tube dependent patients following an acute stroke, during inpatient rehabilitation.…”
Section: Other Interventionsmentioning
confidence: 97%
“…In a study by Xia et al (2011), 120 post stroke patients who exhibited dysphagia were randomly assigned to receive either traditional swallowing treatment, solely NMES, or NMES in conjunction with traditional swallowing management. (67)The researchers found that the individuals who received NMES along with traditional treatment made significantly greater improvements in all four-outcome measures, as opposed to the group who received traditional treatment alone or the group who received NMES alone. Another study by Kushner, et al (2013) examined the effect of NMES use with feeding tube dependent patients following an acute stroke, during inpatient rehabilitation.…”
Section: Other Interventionsmentioning
confidence: 97%
“…After the analysis of the studies, it was found that the application of this questionnaire is more effective when evaluating the result of the overall score, comparing the presence or absence of Parkinson's disease. Therefore, the use of SWAL-QOL in parkinsonian individuals may provide relevant information to the health professional about swallowing and other manifestations due to changes in this function, which should be a factor to be decisive in the choice of treatment procedures 26 used the SWAL-QOL protocol to investigate the effects of conventional therapy and neuromuscular electrical stimulation (VitalStim®) in subjects with dysphagia after stroke, and they are divided into three groups: conventional therapy, VitalStim® and conventional therapy associated VitalStim®. They found that after treatment the SWAL-QOL scores in all groups were significantly higher compared to pre-treatment, with properly held the speech exercises for swallowing showed better QoL.…”
Section: Shinn Et Al (2013)mentioning
confidence: 99%
“…Em estudos que utilizaram a EENM motora (LIM et al, 2009;SUN et al, 2013) ou com nível de estimulação individualizado a cada paciente (XIA et al, 2011) como método de tratamento em casos acometidos por AVE, também foi observada melhora significante na gravidade da disfagia após o tratamento, corroborando com os resultados deste estudo. Qualitativamente, é possível confirmar estes achados, uma vez que 4 dos 10 participantes melhoraram após a terapia com EENM, sendo mantida após três meses da reabilitação e, ainda, um paciente melhorou em mais um nível.…”
Section: Discussionunclassified
“…Semelhantemente, Xia et al (2011) verificaram melhora na qualidade de vida relacionada à deglutição após a terapia com EENM com nível de estimulação individualizado a cada paciente associada à terapia convencional em indivíduos pós-AVE.…”
Section: Discussionunclassified
See 1 more Smart Citation